Antibiotic resistance profile of Acinetobacter baumannii isolates identified from blood cultures - Zaid Faris Hasan; Umut Safiye Şay Coşkun (Medical Laboratory Journal)
Background: Acinetobacter baumannii (A. baumannii) has emerged as the predominant etiological agent responsible for bloodstream infections among hospitalized patients. The objective of this study was to evaluate antibiotic resistance in A. baumannii isolates identified from blood cultures. Methods: A retrospective cohort evaluation was conducted on 117 A. baumannii isolates obtained from blood cultures collected between 2018 and 2019 at the Microbiology Laboratory of Tokat Gaziosmanpaşa University Hospital (Türkiye). The blood culture samples were incubated using the BACT-ALERT 3D system (bioMérieux, Durham, NC, USA). Microorganism identification and antibiotic susceptibility testing were performed using the VITEK 2 (bioMérieux, France) automated system. Results: Of the 117 samples, 59.8% were obtained from males and 40.2% from females. A total of 90.6% of blood culture samples were collected from the intensive care unit, and 88.9% of isolates were identified as multidrug-resistant (MDR). The highest resistance was observed against meropenem (99.1%), while the lowest resistance was noted for colistin (17.1%) and tigecycline (27.3%). Resistance to amikacin was 74.4%, while resistance levels to gentamicin, tobramycin, cefoxitin, and cefotaxime were within the range of 80–90%. Resistance to imipenem, amoxicillin/clavulanic acid, ampicillin/sulbactam, ceftazidime, cefepime, ciprofloxacin, levofloxacin, meropenem, and ertapenem exceeded 90%. Conclusion: The increasing number of MDR A. baumannii isolates poses a significant threat to all hospitalized patients. However, colistin and tigecycline remain preferable options for the treatment of MDR A. baumannii infections. Considering the increasing prevalence of MDR A. baumannii isolates, periodic analysis of epidemiological data in healthcare centers is important for managing resistance to colistin and tigecycline.